Aripiprazole augmentation in highly treatment-resistant obsessive–compulsive disorder – experience from a specialty clinic in India. (2nd January 2017) - Hegde, Aditya; Kalyani, Bangalore G.; Arumugham, Shyam Sundar; Narayanaswamy, Janardhanan C.; Math, Suresh Bada; Reddy, Y. C. Janardhan
Abstract: Objective: To study the effectiveness and tolerability of aripiprazole augmentation in patients with highly treatment-resistant obsessive–compulsive disorder (OCD) in a real-world scenario. Methods: We conducted a chart review of patients who were initiated on aripiprazole augmentation at a specialty OCD clinic in India between 2004 and 2014. Primary outcome measure was all-cause discontinuation. Results: 23 patients were eligible for analysis. Patients had not achieved symptom remission despite a mean of over 3 prior SRI trials. Aripiprazole was continued to be used in seven patients (30%) at the time of last follow-up. Thirteen patients (57%) discontinued the drug due to side effects, and three patients (13%) discontinued aripiprazole citing no improvement. Six patients (26%) were noted to have ≥25% reduction on the Yale-Brown Obsessive–Compulsive Scale. Conclusions: The study demonstrated, in a real-world setting, that aripiprazole may be a useful augmenting agent in a proportion of patients with highly treatment-resistant OCD. However, side effects may lead to premature discontinuation in many of them.